A short course in organic chemistry - Hart, Harolt (Houghton Mifflin, 1959)
Designed specifically for the one-semester short course in organic chemistry, this market leader appeals to a range of non-chemistry science majors through its emphasis on practical, real-life applications of chemistry, coverage of basic concepts, and engaging visual style.